Female athletes explicitly gesture in emotional situations - Adams, Y.; Augenstein, M.; Furley, P.; Krieg, A.; Born, P.; Helmich, I. (Frontiers in Psychology, 2025)
IntroductionBoth appraisal emotion approaches and self-regulation theory emphasize that appraising an event as conducive or detrimental to one’s current goals may trigger an affective response that can be observed nonverbally. Because there may be a female advantage in the inhibition and self-regulation of emotions, we hypothesized that female but not male athletes regulate emotions during sports through explicit nonverbal behaviors.MethodsAll nonverbal hand movement behavior of right-handed female and male tennis athletes was recorded during competitive matches. All immediate nonverbal expressions after point losses and wins were coded by two independent blind raters applying the NEUROpsychological GESture (NEUROGES®) system.ResultsNo gender differences were found for overall hand movement activity. Female athletes executed more fall gestures than males as well as in space and both-handed act as a unit hand movements. In contrast to males, female athletes spent significantly more time with both-handed pantomime gestures (e.g., performing an imaginary backhand), particularly when losing points.DiscussionIncreased expressions of pantomime gestures in female athletes after losing indicate that women regulate negative emotions nonverbally through explicit hand movements. Thus, female athletes seem to nonverbally cope with their negative emotional arousal through explicit nonverbal behaviors in order to control performance.